CADRES COMPETENCE IN COMMUNITY-BASED MANAGEMENT OF CHILD ILLNESS IN BANYUMAS DISTRICT, CENTRAL JAVA, INDONESIA - Umi Solikhah; Hari Kusnanto; Fitri Haryanti; Yayi Suryo Prabandari (Belitung Nursing Journal, 2018)
Background: One of the efforts in the health sector for programs to reduce infant and under-five mortality and morbidity rates is by the competence-based integrated management childhood illness (CB-IMCI) program. However, the program has been poorly implemented by health workers at the health center. Thus, the involvement of cadres is needed and their competency remains important to be improved. Objective: To quantitatively analyze cadre knowledge and competencies in the CB-IMCI program, and its relationship with the implementation of CB-IMCI, as well as to qualitatively explore and analyze the responses of cadres, health workers, and the community to the addition of cadre roles to the management of sick children. Methods: This was a mixed methods study with randomized controlled trials and qualitative method. For randomized controlled trials, 100 cadres were selected, which 50 randomly assigned in the intervention and control group. And for quantitative methods, informants included 10 cadres, 4 health workers, and 20 mothers. Paired t-test and independent t-test were employed for quantitative analysis, and triangulation was used for qualitative analysis. Results: The improvement of knowledge in the intervention group was better (I=14.42/C=4.44/p-value 0.00). The intervention group was more competent in the management of child illness (p-value 0.00). In addition, the cadres have additional competencies assisted by health workers to confidently detect cases earlier, and health center services reach a wider coverage in the community. Conclusion: The addition of cadres’ roles and competencies in the management of child illness in the community can be implemented in Banyumas District. It is suggested that the implementation of this program should be followed up in other health centers by the Health Department of Indonesia.